2023
DOI: 10.1001/jamanetworkopen.2023.0063
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Medication Use Among Older Adults Following Infection-Related Hospitalization

Abstract: ImportanceThere are limited data on discontinuation rates of antipsychotic medications (APMs) used to treat delirium due to acute hospitalization in the routine care of older adults.ObjectiveTo investigate discontinuation rates and patient characteristics of APMs used to treat delirium following infection-related hospitalization among older US adults.Design, Setting, and ParticipantsThis retrospective cohort study was conducted using US claims data (Optum’s deidentified Clinformatics Data Mart database) for Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
3
1
Order By: Relevance
“…In addition, we did not find obvious correlation between body temperature, smoking and drug concentration. This is inconsistent with previous studies that have demonstrated that drug concentration is also correlated with individual factors such as age, sex, and smoking ( 45 48 ). Studies have reported that polycyclic aromatic hydrocarbons in tobacco smoke can affect CYP1A2 ( 49 , 50 ) and smokers who take the same dose of clozapine orally have lower concentrations than non-smokers ( 51 – 53 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, we did not find obvious correlation between body temperature, smoking and drug concentration. This is inconsistent with previous studies that have demonstrated that drug concentration is also correlated with individual factors such as age, sex, and smoking ( 45 48 ). Studies have reported that polycyclic aromatic hydrocarbons in tobacco smoke can affect CYP1A2 ( 49 , 50 ) and smokers who take the same dose of clozapine orally have lower concentrations than non-smokers ( 51 – 53 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The Optum's de-identified Clinformatics® Data Mart Database (CDM), is a de-identified, HIPAA-compliant, closed system of administrative health claims that includes claims for approximately 67 million commercial and Medicare beneficiaries from all 50 U.S. states. This database includes information on patient demographics including zip code, race and ethnicity captured administratively, medical claims, pharmacy claims, and inpatient confinement claims [ [5] , [6] , [7] , [8] ]. This study was deemed exempt from Indiana University institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…1 A fraction of patients are initiated on antipsychotics during critical illness (including sepsis-and infection-related hospitalizations), which are sometimes continued after discharge. 2,3 In Canada, patient and staff safety, management of agitation, sleep disorders and sedation were identified as triggers of antipsychotic treatment in such setting. 4 Antipsychotics have been associated with higher rates of infection (e.g., pneumonia).…”
Section: Purposementioning
confidence: 99%
“…Adult sepsis survivors present with a high risk of long‐term poor clinical outcomes, including recurrent sepsis 1 . A fraction of patients are initiated on antipsychotics during critical illness (including sepsis‐ and infection‐related hospitalizations), which are sometimes continued after discharge 2,3 . In Canada, patient and staff safety, management of agitation, sleep disorders and sedation were identified as triggers of antipsychotic treatment in such setting 4 .…”
Section: Purposementioning
confidence: 99%